2020
DOI: 10.1186/s10194-020-01205-3
|View full text |Cite
|
Sign up to set email alerts
|

Gray and white matter abnormalities in primary trigeminal neuralgia with and without neurovascular compression

Abstract: Purpose Previous researches have reported gray and white matter microalterations in primary trigeminal neuralgia (TN) with neurovascular compression (NVC). The central mechanism underlying TN without NVC are unknown but may include changes in specific brain regions or circuitries. This study aimed to investigate abnormalities in the gray matter (GM) and white matter (WM) of the whole brain and the possible pathogenetic mechanism underlying this disease. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…The present study employed 3D T2-SPACE images to examine cortical/subcortical brain GMVs based on VBM analysis. A previous study reported that patients with TN had greater GMVs in the thalamus, contralateral S1, amygdala, frontal pole, PAG, primary motor cortex, and basal ganglia and cortical thinning in the orbitofrontal cortex, pregenual ACC, and insula [ 29 ], whereas anther study reported that patients with TN showed GMV reductions including the frontal, temporal, and parietal areas, as well as in the left thalamus and right cerebellum [ 30 ]. Our study found that patients with TN had significantly lower GMVs in PCC, ACC, insula, amygdala, and S1 in the affected side compared with the contralateral side before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The present study employed 3D T2-SPACE images to examine cortical/subcortical brain GMVs based on VBM analysis. A previous study reported that patients with TN had greater GMVs in the thalamus, contralateral S1, amygdala, frontal pole, PAG, primary motor cortex, and basal ganglia and cortical thinning in the orbitofrontal cortex, pregenual ACC, and insula [ 29 ], whereas anther study reported that patients with TN showed GMV reductions including the frontal, temporal, and parietal areas, as well as in the left thalamus and right cerebellum [ 30 ]. Our study found that patients with TN had significantly lower GMVs in PCC, ACC, insula, amygdala, and S1 in the affected side compared with the contralateral side before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The present study employed 3D T2-SPACE images to examine cortical/subcortical brain GMVs based on VBM analysis. A previous study reported that patients with TN had greater GMVs in the thalamus, contralateral S1, amygdala, frontal pole, PAG, primary motor cortex, and basal ganglia and cortical thinning in the orbitofrontal cortex, pregenual ACC, and insula [29], whereas anther study reported that patients with TN showed GMV reductions including the frontal, temporal, and parietal areas, as well as in the left thalamus and right cerebellum [30]. Our study found that patients with TN had signi cantly lower GMVs in PCC, ACC, insula, amygdala, and S1 in the affected side compared with the contralateral side before treatment.…”
Section: Discussionmentioning
confidence: 94%
“…They observed significantly lower gray matter volume and cortical thickness in TN with NVC than in TN without NVC (Wu et al, 2020). Moreover, they observed extensive alterations in white matter integrity (Wu et al, 2020). DeSouza et al, using diffusion tensor imaging data, also found abnormalities in brain white matter: lower FA, and higher RD, AD, and MD.…”
Section: Brain White and Gray Matter Changesmentioning
confidence: 95%
“…They employed voxel-based and surface-based morphometry to analyze whole-brain gray matter quantitatively. They observed significantly lower gray matter volume and cortical thickness in TN with NVC than in TN without NVC (Wu et al, 2020 ).…”
Section: Brain White and Gray Matter Changesmentioning
confidence: 99%